Intellectual capital and bank risk in Vietnam: A quantile regression approach - Dat T. Nguyen; Tu DQ Le; Tin H. Ho (Journal of Risk and Financial Management, 2021)
This study empirically presents evidence of nonlinearity and heterogeneity relation between intellectual capital and risk-taking for the Vietnamese banking system. We used quantile regression methods on a data set of 30 Vietnamese banks from 2007 to 2019. The results showed that bank insolvency was positively affected by its value-added intellectual coefficient (VAIC) at the upper quantiles (i.e., 80th and 90th), while the opposite was true for credit risk (i.e., 10th and 20th quantiles). When observing the VAIC's components, risk-taking behaviors were also significantly affected by HCE (Human Capital Efficiency), CEE (Capital Employed Efficiency) and SCE (Structural Capital Efficiency) at the 90th quantile of instability distribution and the 10th quantile of credit risk distribution. Furthermore, the results also emphasized that there was an inverse U-shaped association between intellectual capital and bank risk-taking. Therefore, this study provides important implications for policymakers, regulators, bank managers and academics that encourage increasing investment in knowledge assets to minimize bank risks in the long run.
Keywords: 330; intellectual capital; bank risk-taking; Vietnam; quantile regression